The role of knowledge management in achieving administrative innovation A study of sample of employees of administrative staff at the faculty of economic and administration - Duhok University - Ali, Ari M. (Humanities Journal of University of Zakho, 2016)
Knowledge management consider one of crucial aspects which researchers highlight it from different aspects in order to enrich the subject and get benefit from previous studies from organization. Management letterer reviews pointed that organization with organizational culture and systems are more able to be innovative ant it’s a successful organizations. Because of the innovation role to create new products it consider the depended variable in this study. The research use expletory model to analyze the variables and a questionnaire been made to collect primary data ,and using frequencies ,St. deviation ,mean, regression and correlation by SPSS 18 to conduct the result and test hypothesis .